Effects of cyclic shear stress and average shear stress on the cyclic loading failure of marine silty sand - J. M. Kim; S. W. Son; T. G. Ryu; G. M. Soriano (Lowland Technology International, 2015)
This paper presents the cyclic direct simple shear (CDSS) tests to explain the long term cyclic behavior of marine soil deposits. Cyclic behavior of marine soil deposits depend on the number of loading cycles, vertical effective stress, cyclic shear strain amplitude, relative density, and cyclic and average shear stresses. In addition, the study investigates the effect of cyclic and average shear stresses on the cyclic behavior of marine soil deposits subjected to long term cyclic loading. Design graphs are plotted from the CDSS test results. These results are then modeled and can be used to design offshore structures such as offshore wind turbine foundations, and also used to assess the cyclic shear strength of soil beneath the foundation.